Exploration of factors impacting caregivers' comfort discussing sexuality with ASD youth - Jensen, Spencer Lynn, author; Hepburn, Susan, advisor; Quirk, Kelley, advisor; Dockendorff, Kari, committee member (Colorado State University. Libraries, 2023)
The present study aims to understand factors impacting caregivers' comfort and education goals related to their autistic youth's sexuality through secondary data analysis. Individuals with Autism Spectrum Disorder (ASD) are a vulnerable group to sexual victimization and experience unique psychosexual development. There is little known about sex education efficacy for autistic individuals and how to support caregivers' comfort in addressing issues of sexuality with their youth. This study utilizes secondary analysis of pre-intervention data collected prior to a small (n = 8) pilot study for a sexuality education intervention for parents of autistic youth in 2006. In this project, the following questions will be addressed via narrative analysis and visual inspection: what are caregivers' goals for their autistic youth related to sexuality/sex education and what are the factors impacting caregiver's comfort in talking about their autistic youth's sexuality? Results highlight the heterogeneity of individuals with ASD suggest the need for multi-level and multi-system interventions to promote healthy psychosexual development for autistic youth as sexuality is impacted by several systems and impacts several domains of functioning. Lastly, implications and future directions for research and clinical practice will be discussed.
Keywords: parents; sexuality; sex education; autism spectrum disorder (ASD)